BLOOD BIOCHEMICAL HEPATIC PROFILE IN THE COATI (NASUA NASUA) REARED IN CAPTIVITY - Yupanqui C., Carmen (2008)
The objective of this study was to establish reference serum values for alanine aminotransferase (ALT), aspartate aminotransferase (AST), bilirubin (total and direct), alkaline phosphatase, total proteins and albumin in captive South American coati (Nasua nasua). A total of 19 coatis (11 males and 8 females) from two zoo parks in the area of Lima, Peru were blood sampled. The coatis were chemically restrained using ketamine clorhidrate (10 mg/kg body weight) and xilacine clorhidrate (1 mg/kg body weight) via IM. Blood samples (4 ml) were collected through femoral vein puncture using vacutainer tubes without anticoagulant. The blood chemistry values obtained were ALT: 94.0 ± 48.5 UI/L, AST: 124.7 ± 49.4 UI/L, total bilirubin: 0.72 ± 0.55 mg/dl, direct bilirubin: 0.19 ± 0.21 mg/dl, indirect bilirubin: 0.52 ± 0.52 mg/dl, alkaline phosphatase: 46.8 ± 26.4 UI/L, total proteins: 8.0 ± 1.1 g/dl, and albumin: 3.9 ± 0.5 g/dl.